2022
DOI: 10.3390/ijms231810270
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the WRKY Gene Family and Characterization of Stress-Responsive Genes in Taraxacum kok-saghyz Rodin

Abstract: WRKY transcription factors present unusual research value because of their critical roles in plant physiological processes and stress responses. Taraxacum kok-saghyz Rodin (TKS) is a perennial herb of dandelion in the Asteraceae family. However, the research on TKS WRKY TFs is limited. In this study, 72 TKS WRKY TFs were identified and named. Further comparison of the core motifs and the structure of the WRKY motif was analyzed. These TFs were divided into three groups through phylogenetic analysis. Genes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Herein, a total of 42 GmWRKYs were obtained from the G. macrophylla genome by bioinformatics analysis and divided into 3 groups (12 in Group I, 25 in Group II, and 5 in Group III). Obviously, group II was the largest group in G. macrophylla , which was similar to the results of Panax ginseng [ 28 ], Eucommia ulmoides [ 48 ], Taraxacum kok-saghyz [ 49 ] and Bupleurum chinense [ 50 ]. Considering that the distribution discrepancy of the groups implied different evolutionary processes in plant development [ 48 , 51 ], the above data indicated that GmWRKYs in group II underwent more gene duplications during the process of evolution.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Herein, a total of 42 GmWRKYs were obtained from the G. macrophylla genome by bioinformatics analysis and divided into 3 groups (12 in Group I, 25 in Group II, and 5 in Group III). Obviously, group II was the largest group in G. macrophylla , which was similar to the results of Panax ginseng [ 28 ], Eucommia ulmoides [ 48 ], Taraxacum kok-saghyz [ 49 ] and Bupleurum chinense [ 50 ]. Considering that the distribution discrepancy of the groups implied different evolutionary processes in plant development [ 48 , 51 ], the above data indicated that GmWRKYs in group II underwent more gene duplications during the process of evolution.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to AtWRKYs in A. thaliana [ 56 ] and TkWRKYs in Taraxacum kok-saghyz [ 49 ], most GmWRKYs contained a WRKY domain prominent feature composed of 60 amino acids with a conserved WRKYGQK heptapeptide sequence at the N-terminus. In most cases, the WRKY domain was very conserved; however, variant motifs such as WRKYGEK, WRKYGKK, WRICGQK, WSKYEQK and WRKYSEK were also found [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that many genes can be divided according to their abundant expressions in specific organs, a finding that might reflect their participation in the common developmental processes ( Sun et al, 2020 ). Four genes ( DoWRKY20 , - 33 , - 21 , - 71 ) significantly upregulated during cold stress, and their responses are comparable to those of 8 TkWRKY genes which were induced by cold stress ( Cheng et al, 2022 ). Under ABA stress, four DoWRKY genes ( DoWRKY33 , - 21 , - 70 and - 71 ) were significantly induced.…”
Section: Discussionmentioning
confidence: 84%
“…Further, the distribution of 11 representative cis -acting regulatory elements in promoter regions was investigated. Based on their functions, these cis -acting elements were divided into three categories: category 1 included motifs related to hormone response (ABRE, P-box, TATC-box, TGACG-motif, AuxRR-core, TGA-element), and category 2 had motifs related to environmental stress (WUN-motif, TC-rich repeats, LTR and MBS), while category 3 included motifs related to development (MBSI) [ 32 , 46 , 47 ]. The analysis showed that abundant cis -acting elements were distributed in the promoter regions of CeqWRKYs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cis -element analysis showed that, compared to the promoter region of WRKY genes from Taraxacum kok-saghyz and Liriodendron chinense, CeqWRKYs promoter region contained much more hormone response elements, including ABRE, MeJA, and stress related elements, such as W-box (WRKY transcription factor binding site), and TC-rich (salt stress-related elements) (Fig. 3 B, Figure S 1 ) [ 46 , 58 ], inferring that CeqWRKYs are involved in ABA- and MeJA-mediated stress responses.…”
Section: Discussionmentioning
confidence: 99%